PENGOLAHAN LIMBAH PERTANIAN DAN KERAJINAN MENJADI PUPUK ORGANIK BERKUALITAS DI DESA TARO, KECAMATAN TEGALLALANG KABUPATEN GIANYAR - Suwastika, A.A.N.G.; Sutari, N. W. S.; Sunari, A.A.A.A. S.; Soniari, N.N.; Atmaja, I W. D. Atmaja (Buletin Udayana Mengabdi; Vol 12 No 1 (2013): Volume 12 No.1 – April 2013, 2013)
This community service was held on Thursday, July 26, 2012 at Gapoktan Sarwa Ada”, the village of Taro, Tegallalang District, Gianyar regency. The method used in this activity through education and training with the aim at improving farmers’ knowledge in the processing agricultural waste and waste wood craft a quality organic fertilizer to use local microorganisms. Training wass going well and in the family atmosphere. Material extension and how to manufacture quality organic fertilizer were easily understood by farmers. All farmers can make their own organic fertilizer from organic waste. Preparation of local microorganisms as decomposers bioactivator was easy to handle. Knowledge of farmers on organic waste still needs to be improved to prevent environmental pollution.